Alkaline thermal sludge hydrolysis - Neyens, E; Baeyens, J; Creemers, C (Journal of hazardous materials, 2003)
The waste activated sludge (WAS) treatment of wastewater produces excess sludge which needs further treatment prior to disposal or incineration. A reduction in the amount of excess sludge produced, and the increased dewaterability of the sludge are, therefore, subject of renewed attention and research. A lot of research covers the nature of the sludge solids and associated water. An improved dewaterability requires the disruption of the sludge cell structure. Previous investigations are reviewed in the paper. Thermal hydrolysis is recognized as having the best potential to meet the objectives and acid thermal hydrolysis is most frequently used, despite its serious drawbacks (corrosion, required post-neutralization, solubilization of heavy metals and phosphates, etc.). Alkaline thermal hydrolysis has been studied to a lesser extent, and is the subject of the detailed laboratory-scale research reported in this paper. After assessing the effect of monovalent/divalent cations (respectively, K +/Na + and Ca 2+/Mg 2+) on the sludge dewaterability, only the use of Ca 2+ appears to offer the best solution. The lesser effects of K +, Na + and Mg 2+ confirm previous experimental findings. As a result of the experimental investigations, it can be concluded that alkaline thermal hydrolysis using Ca(OH) 2 is efficient in reducing the residual sludge amounts and in improving the dewaterability. The objectives are fully met at a temperature of 100 °C; at a pH≈10 and for a 60-min reaction time, where all pathogens are moreover killed. Under these optimum conditions, the rate of mechanical dewatering increases (the capillary suction time (CST) value is decreased from approximately 34 s for the initial untreated sample to approximately 22 s for the hydrolyzed sludge sample) and the amount of DS to be dewatered is reduced to approximately 60% of the initial untreated amount. The DS-content of the dewatered cake will be increased from 28 (untreated) to 46%. Finally, the mass and energy balances of a wastewater treatment plant with/without advanced sludge treatment (AST) are compared. The data clearly illustrate the benefits of using an alkaline AST-step in the system.